An Analysis of Basic Human Values in the C.S Lewis’ the Chronicles of Narnia: the Lion, the Witch and the Wardrobe - Muliani, Ari (Universitas Pendidikan Ganesha, 2022)
The purpose of this study was to identify basic human values on C.S Lewis’ novel “The Chronicles of Narnia: The Lion, The Witch, and The Wardrobe. Textual analysis was used in this study. The data were collected by reading the text and creating data corpus units in written form. There are 24 basic human values that can be found in this novel. The basic human values are self-direction (curiosity) and hedonism (enjoyment/pleasure), power (authority), security (safety), tradition (belief), benevolence (loyalty), stimulation (bravery and love challenge), achievement (ambition), and benevolence (helpful and forgiveness), self-direction (independence, creativity, and self-respect), stimulation (pleasure/enjoyment), achievement (success and capability), conformity (positive behavior and harmony), tradition (religion), and universalism (tolerance and wisdom).